2010
DOI: 10.1107/s0108767310014236
|View full text |Cite
|
Sign up to set email alerts
|

Multipole electron-density modelling of synchrotron powder diffraction data: the case of diamond

Abstract: Accurate structure factors are extracted from synchrotron powder diffraction data measured on crystalline diamond based on a novel multipole model division of overlapping reflection intensities. The approach limits the spherical-atom bias in structure factors extracted from overlapping powder data using conventional spherical-atom Rietveld refinement. The structure factors are subsequently used for multipole electron-density modelling, and both the structure factors and the derived density are compared with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 51 publications
10
47
0
Order By: Relevance
“…We have developed a method for determining accurate charge densities using multiple overlaid SR powder data sets [8,9,10]. The error of the structure factors determined by the method is less than 1.0%, which is comparable to that of the very accurate Pendellösung method [11].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…We have developed a method for determining accurate charge densities using multiple overlaid SR powder data sets [8,9,10]. The error of the structure factors determined by the method is less than 1.0%, which is comparable to that of the very accurate Pendellösung method [11].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…For the more detailed analysis of charge densities, a combination of the MEM analysis with the multipole modelling [46] is preferable, in which wider Q range data are needed to optimize a large number of fitting parameters.…”
Section: Characteristics Of the Mem Charge Density Studiesmentioning
confidence: 99%
“…The vast majority of experimental ED studies are based on modelling of structure factors obtained from single-crystal X-ray diffraction (Koritsanszky & Coppens, 2001;Coppens et al, 2005). However, in a previous study of diamond, we showed that application of the HC model is also feasible in the case of powder diffraction data (Svendsen et al, 2010). There are pros and cons for both single-crystal and powder diffraction studies and, in the latter case, background subtraction as well as peak overlap have generally been considered as insurmountable challenges to the multipolar method.…”
Section: Introductionmentioning
confidence: 98%
“…In recent studies we explored the current limits of the X-ray ED method (Svendsen et al, 2010;Schmøkel et al, 2013). The vast majority of experimental ED studies are based on modelling of structure factors obtained from single-crystal X-ray diffraction (Koritsanszky & Coppens, 2001;Coppens et al, 2005).…”
Section: Introductionmentioning
confidence: 99%